2010
DOI: 10.1016/j.aquatox.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytochrome P450 1 genes and stress response genes in developing zebrafish exposed to ultraviolet radiation

Abstract: Ultraviolet (UV) radiation damages cell molecules, and has been suggested to upregulate mammalian cytochrome P4501 (CYP1) genes through an aryl hydrocarbon receptor (AHR) mediated mechanism. In this study, embryos and larvae of zebrafish (Danio rerio) were exposed to UV to determine the effects on expression of CYP1 and stress response genes in vivo in these fish. Zebrafish embryos were exposed for varying times to UV on two consecutive days, with exposure beginning at 24 and 48 hours post-fertilization (hpf).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
(68 reference statements)
1
20
1
Order By: Relevance
“…Although CYPs (cytochrome P450s) are well known for their role in aryl hydrocarbon metabolism in the liver, studies have shown that it also has an essential role in vitamin D signaling, which regulates hundreds of genes in many physiological functions including the immune response (Schartl et al, 2013). Furthermore, our finding also correlates with the previous study showing that CYP 1 genes appear to be up-expressed at moderate dose (20.1 kJ/m 2 ) but not at higher dose (26.8 kJ/m 2 ) in UVB exposure of developing zebrafish (Behrendt et al, 2010). From methionine and ATP, MAT1A catalyzes the formation of S-adenosylmethionine, which is the main methyl donor for a vast number of methylation processes (Chiang et al, 1996).…”
Section: Resultssupporting
confidence: 92%
“…Although CYPs (cytochrome P450s) are well known for their role in aryl hydrocarbon metabolism in the liver, studies have shown that it also has an essential role in vitamin D signaling, which regulates hundreds of genes in many physiological functions including the immune response (Schartl et al, 2013). Furthermore, our finding also correlates with the previous study showing that CYP 1 genes appear to be up-expressed at moderate dose (20.1 kJ/m 2 ) but not at higher dose (26.8 kJ/m 2 ) in UVB exposure of developing zebrafish (Behrendt et al, 2010). From methionine and ATP, MAT1A catalyzes the formation of S-adenosylmethionine, which is the main methyl donor for a vast number of methylation processes (Chiang et al, 1996).…”
Section: Resultssupporting
confidence: 92%
“…Several studies have reported on transcription factors related to UVA radiation stress in organisms. For example, transcription factor AP-2, NF-E2-related factor 2, HSP family, and P450 family are involved in the transcriptional response induced by UVA radiation (GretherÐBeck et al 1996, Behrendt et al 2010, Gruber et al 2010, Sang et al 2012. In our study, these eight potential TFBMs observed for the UVA-associated genes may play important roles in protecting insects against challenge with UVA radiation stress.…”
Section: Figmentioning
confidence: 71%
“…Phase II drugmetabolizing enzymes play an important role in the biotransformation of endogenous compounds and free radicals to more easily excretable forms as well as in the metabolic inactivation of pharmacologically active compounds. The adverse effects of nonionizing radiation are partially reduced by molecular defense mechanisms including GSH and enzymes such as superoxide dismutase, catalase, and glutathione peroxidase, which are involved in quenching excessive levels of ROS and other free radicals (Behrendt et al 2010). GSTs are multi-gene families of enzymes involved in the metabolism of a wide range of electrophilic compounds of both exogenous and endogenous origin.…”
Section: Discussionmentioning
confidence: 99%